Simple brushless DC motor drive for solar photovoltaic array fed water pumping system. Issue 7 (1st June 2016) - Singh, Bhim; Kumar, Rajan
Abstract : This study deals with a buck–boost converter controlled solar photovoltaic (SPV) array fed water pumping in order to achieve the maximum efficiency of an SPV array and the soft starting of a permanent magnet brushless DC (BLDC) motor. The current sensors normally used for speed control of BLDC motor are completely eliminated. The speed of BLDC motor is controlled through the variable DC‐link voltage of a voltage‐source inverter (VSI). The VSI is operated by fundamental frequency switching, avoiding the losses due to high‐frequency switching, in order to enhance the efficiency of the proposed system. The dynamic and steady‐state behaviours of the proposed system are demonstrated under rapid variations in atmospheric conditions. An experimental validation is also made to validate the design and simulated results under real circumstances on a developed prototype.